HUBUNGAN PELAKSANAAN SCREENING TEST MENELAN DENGAN KEJADIAN DISFAGIA PADA PASIEN BARU YANG MENDERITA STROKE AKUT - Muhammad Arif (JURNAL KESEHATAN PERINTIS, 2017)
According to the NINDS 2015, States that a stroke occurs when the blood supply to brain fails suddenly interrupted due to a blockage or rupture of blood vessels were. Basic Health Research results that show an increase in the prevalence of stroke symptoms in Indonesia increased from 8.3 at 1000 in 2007 to 12.1 and at 1000 in 2013. One of the problems that arise due to stroke is a disorder of swallowing or dysphagia. According to the World Stroke Academy Learning Moduls in 2012 the prevalence of dysphagia in stroke sufferers range from 36 to 67%. In the year 2016 in RSSN dysphagia in stroke patients 22,94%. For early detection of dysphagia screening test required to swallow as a first step in identifying the risks due to dysphagia and aspiration in stroke patients. The purpose of this research is to know the relationship of the implementation of the screening test to swallow with dysphagia in acute stroke patients in the room just entered inpatient Neurology RSSN Bukittinggi in 2017. This research method using analytic, descriptive, then the data was processed using the Chi Square test. The sample in this study as many as 54 people respondents. Test result statistics retrieved value p value = 0.002 (p < α) then it can be inferred the existence of a relationship between the implementation of the screening test to swallow with dysphagia in acute stroke patients the new entry. Analysis of the results obtained OR = 9.281 meaning respondents who perform screening test procedures in accordance with the swallow has a chance of 9.281 times in detecting the occurrence of dysphagia. Suggestions in this study is the implementation of a screening test this swallow can be included in SPO for nurses in Bukittinggi in the room especially RSSN Neurology in detecting the onset of dysphagia in acute stroke patients.